قياس أثر التطور المالي على النمو الاقتصادي في ليبيا للفترة 1980-2023 باستخدام نموذج Augmented ARDL (Comprehensive Journal of Science, 2026)
This study investigates the impact of financial development on economic growth in Libya over the period 1980-2023, financial indicators employed in the analysis include: domestic credit to GDP, credit to the privet sector to GDP, money supply to GDP, and deposit volume to GDP. Unit root test results indicate that the study variables are stationary at both levels and first differences, whereas the dependent variable (GDP growth) is stationary at level. Consequently, the Augmented ARDL model was employed. The findings of the Bounds test confirm the absence of a long-run equilibrium relationship between financial development indicators and economic growth. Moreover, the results reveal no evidence of a causal relationship among the examined variables. The study future suggests that the banking sector has played a limited role in fostering economic growth during the study period. Accordingly, the paper emphasizes the necessity of adopting targeted policies aimed at enhancing the effectiveness of the banking system in promoting overall economic development.